In the Tradition or Outside? Reflections on Teachers and Influences - Martin van Bruinessen (Al-Jami'ah: Journal of Islamic Studies, 2015)
In this autobiographical essay, Martin van Bruinessen looks back at the diverse intellectual influences that contributed to his formation as a scholar of Indonesian Islam. He was never trained as an Indonesianist or a scholar of Islam, and came to the subject through a series of unplanned changes in his life trajectory. His first acquaintance with Indonesia was through late colonial and post-colonial Dutch literature. It was followed in his student days by critical reporting on the massacres of 1965-66 and a re-reading of Indonesian history from an anti-imperialist viewpoint. His formal academic training was in entirely different disciplines, and his first experience with anthropological fieldwork took place in a different part of the world. A fortuitous post-doctoral appointment at KITLV, followed by four years at LIPI as a consultant for research methods, enabled him to acquaint himself directly with contemporary Muslim discourses and movements. He had the good fortune of working with leading Indonesian Muslim intellectuals, who became his major teachers. Only when he became a teacher and thesis supervisor himself, at the IAIN Sunan Kalijaga and later at Utrecht University, did he feel the need to reflect on how his own research relates to established academic traditions. The essay documents his growing appreciation of, and lasting critical distance from, the Leiden school of Oriental studies and his relationship with the French tradition of Islamic and Indonesian studies. It also attempts to be the story of the rise and decline of Leiden’s tradition of Indonesian Islamic studies, from the perspective of a critical reader who wishes to remain an outsider.[Dalam tulisan biografis ini, Martin van Buinessen melihat kembali beberapa pengaruh pembentukan dirinya sebagai sarjana tentang Islam Indonesia. Martin tidak belajar khusus tentang keindonesiaan atau keislaman, minat itu muncul dari perubahan-perubahan dalam hidupnya. Perkenalannya dengan Indonesia dimulai lewat tulisan-tulisan dari masa akhir dan pasca penjajahan. Pengalamannya berlanjut pada masa studinya saat menulis laporan kritis tentang kasus 1965-1966 dan dengan pembacaan ulangnya atas sejarah Indonesia dari sudut pandang anti imperalisme. Latar belakang pendidikan formalnya sama sekali berbeda, sementara pengalaman pertama riset antropologinya juga di tempat yang berbeda. Posisi post-doktoral di KITLV dan diikuti empat tahun di LIPI sebagai konsultan metodologi riset membuat Martin bersinggungan langsung dengan wacana muslim kontemporer dan gerakannya. Martin sangat beruntung bertemu dengan para cendikiawan muslim Indonesia yang kemudian menjadi guru-gurunya. Dari pengalamannya menjadi dosen dan supervisor disertasi di IAIN Sunan Kalijaga, sekarang UIN Sunan Kalijaga, dan selanjutnya di Universitas Utrecht juga, Martin merasa perlu untuk merefleksikan kembali penelitiannya dalam kaitannya dengan tradisi akademik yang mapan. Tulisan ini mendokumentasikan perkembangan apresiasinya, sekaligus kritiknya, terhadap studi ketimuran mazhab Leiden serta keterkaitannya dengan studi keislaman dan keindonesiaan dalam tradisi Perancis. Ini juga merupakan upaya untuk menulis sejarah naik-turunnya studi keislaman Indonesia mazhab Leiden dari perspektif seorang pembaca kritis yang berusaha tetap menjadi ‘orang luar’.]